In the Wake of the Quiet Revolution: From Secularization to Religious Cosmopolitanism - Meintel, Dierdre; Mossière, Géraldine (Anthropologica, 2013)
Montréal’s current religious landscape reflects cer tain historical and social factors that contributed to the develop ment of a somewhat unique "religious cosmopolitanism" in the city. We explore the notion of religious cosmopolitanism and how it manifests in the Montréal context, drawing on the results of team research involving the ethnographic study of 100 religious groups in the metropolitan area. In so doing, we present an image of religious openness on the part of the Québécois, at least on the part of those who frequent religious or spiritual groups, which contrast with the secularism being promoted by the Parti Québécois and with media images of Québec as closed to religious diversity.